Financial Performance Analysis of Mendalo Laut Village Government, Muaro Jambi, 2020–2023 - Bella Ranita Putri; Sri Rahayu; Yuliusman Yuliusman (Harmoni Economics: International Journal of Economics and Accounting, 2025)
This investigate points to analyze the Budgetary Execution of the Mendalo Laut Town Government, Jambi Exterior City Area, Muaro Jambi Rule for the Monetary Year 2020-2023.This think about points to decide the Money related Execution of Mendalo Laut Town utilizing the Decentralization Degree Proportion, Town Budgetary Autonomy Proportion, Town Money related Reliance Proportion, PADes Adequacy Proportion, Use Proficiency Proportion, Use Agreement Proportion, and PADes Development Ratio.This inquire about may be a quantitative expressive study.Using auxiliary information within the shape of the Realization Report of the Town Income and Consumption Budget (APBDes) of Mendalo Laut Town, Jambi External City Area, Muaro Jambi Rule for the 2020-2023 Monetary Year.The inquire about comes about appear that the Budgetary Execution of the Mendalo Laut Town Government based on the Degree of Decentralization Proportion is categorized as exceptionally destitute, the Town Monetary Autonomy Proportion is categorized as Exceptionally Moo, the Town Monetary Reliance Proportion is categorized as exceptionally tall, the PADes Viability Proportion is categorized as ineffectual, the Investing Concordance Proportion is categorized as destitute, and the PADes Development Proportion is categorized as Not Great. Furthermore, the SWOT Examination employments the S-O technique, which utilizes inner qualities to abuse outside openings.